THE INTRA-PROPOSITIONAL OPERATIONS AND NUMBER - Serrano, José Manuel; Pons, Rosa María (Anales de Psicología / Annals of Psychology, 2008)
This research expects to confirm the ordinal-cardinal indisocia-bility of the number offered by Piaget, just like the origin of this instrument of assimilation of the real. It is widely analyzed the schemes of classification, from both a logic perspective as a mereologic one, and the ordinal processes of quantization. The outcome show up that the number however has a cardinal component and an ordinal one, the second is more pure than the first one in the psychogenesis, and that both components are insufficient to explain the numerical execution of children.